Correlations between selected fatness indices and total body fat estimated by means of the impedance method - Socha, Małgorzata (Anthropological Review, 1999)
The aim of the present work was the evaluation of measures of total body fat and distribution of adipose tissue, including the new conicity index, and their correlation with total body fat (in kg and %) estimated by means of the impedance method. Moreover, attention was paid to the bilateral differentiation of fat distribution. The basis for the analyses and comparisons was a group of 186 females of various age. Using cluster analysis and factor analysis for fatness measures, it was shown that the measures under study form two distinctly separate groups referring to different aspects of fatness: total body fat, and adipose tissue distribution.